Internet service provider liability for copyright and trade mark infringement : towards an EU co-regulatory framework - Krokida, Zoi (London [England] : Hart Publishing, 2022)
"This book critically evaluates the EU regulatory framework for the liability of host Internet Service Providers (ISPs) for copyright and trade mark infringements and provides a cluster of novel recommendations for its improvement. The book recommends the imposition of a duty of care to host ISPs to curb the dissemination of unauthorised works and counterfeit goods, the ascription of a transparency obligation to host ISPs towards their users, and the establishment of a supervisory authority for host ISPs. Host ISPs have facilitated the dissemination of content amongst users and the purchase of goods online, enabling copyright holders and brand owners to attract a greater audience for their works and goods. However, their services have attracted a high number of copyright and trade mark violations, too. Neither Article 14 of the e-Commerce Directive nor Article 17 of the Copyright in the Digital Single Market Directive provide a solid response to the issue of host ISPs' liability. This book is a valuable resource for researchers in IT and IP law and offers a new perspective for resolving online IP disputes."--
Acknowledgements -- List of Abbreviations -- List of Cases -- Introduction -- Part I: Theoretical and Policy Considerations -- 1. Internet Regulatory Theories: Historical and Theoretical Background -- 2. Liability for Host Internet Service Providers: Theoretical and Policy Background -- Part II: Evaluation of the Current Legislative Tools -- 3. The Host Internet Service Providers' Liability Framework Under Article 14 of the E-Commerce Directive for Trade Mark and Copyright Infringements: An Outdated Approach -- 4. The Regulatory Framework of Online Content Sharing Service Providers Under Article 17 of the Copyright in the Digital Single Market Directive for Copyright Infringements: A Controversial Approach -- Part III: Introducing a Co-Regulatory Framework -- 5. Redefining the Concept of Duty of Care -- 6. Introducing a Statutory Provision for Transparency -- 7. Establishing a Supervisory Authority: A Proposal -- Conclusion
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Internet service providers -- Law and legislation -- European Union countries; Liability (Law) -- European Union countries; Internet -- Law and legislation -- European Union countries; Copyright -- Computer files -- European Union countries; Electronic books